Simultaneous-arrival of multiple agents with different targets - Li, R.; Shi, Y. (IEEE Computer Society, 2014)
In this paper, we study the simultaneous-arrival problem of multi-agent systems, where the multiple agents with distributed protocol will reach same target or different targets. We first introduce the time-estimator for each agent to arrive the target and show the convergence of the time-estimator algorithm by using Lyapunov Theory and Lasalle's Invariance Principle. On this basis, we then establish the simultaneous-arrival control algorithm for multi-agent systems without obstacle. Furthermore, the simultaneous-arrival algorithm with obstacle avoidance is studied. The convergence analyses are given for the proposed simultaneous-arrival protocols. Finally, the simulation results are presented to demonstrate the effectiveness of our theoretical methods in achieving simultaneous-arrival.